Analisis Prediksi Kinerja Bundaran Bancar Purbalingga 5 Tahun Mendatang - Nurhidayat, Rizal Afian; Sari, Cremona Ayu Novita; Fathoni, M. Agus Salim Al (Proceedings Series on Physical & Formal Sciences, 2026)
The growth in population and vehicle numbers in Purbalingga Regency has a direct impact on increasing traffic volume, particularly at unsignalized intersections such as the Bancar Roundabout. This study aims to analyze the current performance and predict the performance of the Bancar Roundabout over the next five years using the Indonesian Road Capacity Guidelines (PKJI) 2023 method. The parameters analyzed include capacity, degree of saturation, delay, and queue probability. Primary data were obtained through traffic surveys conducted over two days, representing weekdays and weekends, while secondary data were collected from relevant agencies. The analysis results indicate that under current conditions, the Bancar Roundabout has the highest degree of saturation of 0.263, an average traffic delay of 5 seconds/PCU, and a maximum queue probability of 5%, which is classified as Level of Service B. The five-year projection shows an increase in traffic volume; however, the roundabouts performance remains stable with the highest degree of saturation at 0.325, an average delay of 6 seconds/PCU, and a maximum queue probability of 7%. This suggests that the roundabout can still function efficiently without the need for geometric modifications in the near future. Regular evaluations are recommended as a precautionary measure against future traffic condition changes.